Assessing the role of Differentiated Instruction in English Language Teaching: A Study Review on Adaptive Learning - V, Parvathy.; Pillai, Radharemanan (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this review paper is to assess the role of differentiated instruction (DI) in English language teaching and learning. The literature survey has been chosen so as to address the objectives of the study which are studying the role of DI in English Language Teaching. It also concentrated in the studying the procedures and techniques undertaken for teaching English. Lastly, this paper also explores the factors affecting DI in classrooms. Secondary sources were used to collect the information needed for this study. The most important finding from the study was that DI has a tremendous positive impact in helping students learn English. Another chief finding was the importance of training teachers in various approaches and methods for implementing differentiated instruction.